On a new method for constructing exact solutions of the nonlinear differential equations of mathematical physics - Barannyk, Anatoliy; Yuryk, Ivan (My University, 1998)
A new method for constructing solutions of multidimensionflnonlinear differential equations is proposed. Запропоновано новий метод побудови розвязків багатовимірних нелінійних диференціальних рівнянь.
Keywords: symmetry reductijn; симетрійна редукція; Dflambert; Liouville; Eikonal equations; exact solutions; рівняння Даламбера; рівняння Ліувілля; рівняння Ейконала; точні розвязки; кафедра вищої математики імені проф. Можара В. І.